Left out but not backing down: exploring women's voices against large-scale agro-plantations in Cameroon. Issue 8 (17th November 2017) - Fonjong, Lotsmart
ABSTRACT: This article examines the situation of women around agro-plantations which have taken over their farmlands in the South-West Region of Cameroon through large-scale land acquisitions, and how they have sought popular redress. Based on a survey and focus group discussion among affected women, the findings revealed that women are generally left out of large-scale land acquisition processes. They complained of displacement from their farms and traditional forest resources, which has negative effects on their livelihoods and lifestyles. Despite women's constrained situation, they have risen collectively against marginalisation, failed promises, and injustices through protests and defiance, achieving some successes in their demands for recognition and compensation.